Exploring Approaches in Green Technical and Vocational Education Training (TVET): A Systematic and Bibliometric Review - Adjei, Albert; Abdullah, Ade Gafar; Ampimah, Benjamin Chris; Bonsu, Prince Osei-; Mulyanti, Budi (Journal of Vocational Education Studies, 2024)
This study identifies and analyzes the main research areas related to green technical and vocational education training (TVET). It focuses on evaluating the extent of its integration into TVET programs. The research explores the link between green TVET, environmental sustainability, and its impact on human development, drawing on research and data from the past decade (2013-2023). This paper aims to offer readers an in-depth insight into progress and prospective developments, with a specific emphasis on the pedagogical approach in Technical and Vocational Education Training (TVET) and stakeholders' concerns in this domain. To achieve this goal, the study applied the Systematic Literature Network Analysis (SLNA) method, combining bibliometric analysis techniques with a systematic literature review (SLR) using the PRISMA approach. This integrated approach utilizes objective measurements and algorithms to discern emerging themes and subjects to gain a thorough understanding of the current state of green TVET and potential paths for further integration to address environmental issues and enhance human capacity. The paper finds that green TVET positively affects learners' knowledge, skills, attitudes, and behaviors related to environmental sustainability, as well as their employability and career prospects in the green economy. It highlights challenges and gaps in implementing and evaluating green TVET, such as the lack of standardized definitions, indicators, and methodologies, insufficient integration of green competencies, and limited stakeholder involvement. The paper concludes with recommendations for policy and practice and directions for future research.